PIMMS (Pragmatic Insertional Mutation Mapping System) laboratory methodology a readily accessible tool for identification of essential genes in Streptococcus - Blanchard, Adam M.; Egan, Sharon A.; Emes, Richard D.; Warry, Andrew; Leigh, James A. (Frontiers, 2016)
The Pragmatic Insertional Mutation Mapping (PIMMS) laboratory protocol was developed alongside various bioinformatics packages (Blanchard et al., 2015) to enable detection of essential and conditionally essential genes in Streptococcus and related bacteria. This extended the methodology commonly used to locate insertional mutations in individual mutants to the analysis of mutations in populations of bacteria. In Streptococcus uberis, a pyogenic Streptococcus associated with intramammary infection and mastitis in ruminants, the mutagen pGhost9:ISS1 was shown to integrate across the entire genome. Analysis of >80,000 mutations revealed 196 coding sequences, which were not be mutated and a further 67 where mutation only occurred beyond the 90th percentile of the coding sequence. These sequences showed good concordance with sequences within the database of essential genes and typically matched sequences known to be associated with basic cellular functions. Due to the broad utility of this mutagen and the simplicity of the methodology it is anticipated that PIMMS will be of value to a wide range of laboratories in functional genomic analysis of a wide range of Gram positive bacteria (Streptococcus, Enterococcus, and Lactococcus) of medical, veterinary, and industrial significance.